Identity-by-descent mapping of recessive traits in livestock: application to map the bovine syndactyly locus to chromosome 15. - Charlier, C; Farnir, F; Berzi, P; Vanmanshoven, P; Brouwers, B; Vromans, H; Georges, M (Genome Research, 1996)
Twelve animals affected with syndactyly or mulefoot were sampled in the Dutch black-and-white cattle population. Analysis of the pedigree data reveal that all of these individuals traced back to a single acknowledged carrier founder individual. Between seven and nine generations separated the founder from its 12 affected descendents. The 12 affected offspring were genotyped for a battery of 213 microsatellites spanning the 29 bovine autosomes. The resulting genotypes were analyzed using a maximum likelihood approach searching for shared homozygous haplotypes among affected individuals. Three candidate regions for the syndactyly locus emerged from this initial screening. syndactyly was shown to map to one of these candidate regions on chromosome 15 by genotyping 29 additional individuals linking founder and affected offspring and performing a conventional linkage analysis with the LINKAGE programs. This study illustrates the potential of identity-by-descent mapping in livestock populations.
10.1101/gr.6.7.580